A Novel Microfluidic Device for the Neutrophil Functional Phenotype Analysis: Effects of Glucose and Its Derivatives AGEs - Ke Yang; Xiao Yang; Chaoru Gao; Changyi Hua; Chenggang Hong; Ling Zhu (Micromachines, 2021)
Neutrophil dysfunction is closely related to the pathophysiology of patients with diabetes mellitus, but existing immunoassays are difficult to implement in clinical applications, and neutrophil’s chemotaxis as a functional biomarker for diabetes mellitus prognostic remains largely unexplored. Herein, a novel microfluidic device consisted of four independent test units with four cell docking structures was developed to study the neutrophil chemotaxis, which allowed multiple cell migration observations under a single field of view (FOV) and guaranteed more reliable results. In vitro studies, the chemotaxis of healthy neutrophils to N-Formyl-Met-Leu-Phe (fMLP) gradient (0, 10, 100, and 1000 nM) was concentration-dependent. The distinct promotion or suppression in the chemotaxis of metformin or pravastatin pretreated cells were observed after exposure to 100 nM fMLP gradient, indicating the feasibility and efficiency of this novel microfluidic device for clinically relevant evaluation of neutrophil functional phenotype. Further, the chemotaxis of neutrophils pretreated with 25, 50, or 70 mM of glucose was quantitatively lower than that of the control groups (i.e., 5 mM normal serum level). Neutrophils exposed to highly concentrated advanced glycation end products (AGEs) (0.2, 0.5, or 1.0 μM; 0.13 μM normal serum AGEs level), a product of prolonged hyperglycemia, showed that the higher the AGEs concentration was, the weaker the migration speed became. Specifically, neutrophils exposed to high concentrations of glucose or AGEs also showed a stronger drifting along with the flow, further demonstrating the change of neutrophil chemotaxis. Interestingly, adding the N-benzyl-4-chloro-N-cyclohexylbenzamide (FPS-ZM1) (i.e., high-affinity RAGE inhibitor) into the migration medium with AGEs could hinder the binding between AGEs and AGE receptor (RAGE) located on the neutrophil, thereby keeping the normal chemotaxis of neutrophils than the ones incubated with AGEs alone. These results revealed the negative effects of high concentrations of glucose and AGEs on the neutrophil chemotaxis, suggesting that patients with diabetes should manage serum AGEs and also pay attention to blood glucose indexes. Overall, this novel microfluidic device could significantly characterize the chemotaxis of neutrophils and have the potential to be further improved into a tool for risk stratification of diabetes mellitus.